Provision of complementary therapy of five-finger hypnosis and provision of education on anxiety in pregnant women - Adnyani, Ni Wayan Sukma; Widiastuti, Ni Made Rai; Sugiartini, Ni Ketut Ayu; Ayuk Widiani, Ni Nyoman; Ari Febriyanti, Ni Made (Poltekkes Kemenkes Bandung, 2026)
Background: Anxiety during pregnancy is common and may negatively affect both mother and fetus. Non-pharmacological approaches, such as relaxation and hypnosis, are increasingly recommended to minimize risks. Objective: This study aimed to assess the effect of five-finger hypnosis combined with health education on anxiety among pregnant women. Methods: A quantitative quasi-experimental study with a one-group pre- and post-test design was conducted at Community Health Center I, West Denpasar, from June to September 2024. Thirty pregnant women were recruited using purposive sampling. Anxiety was measured using the Indonesian version of the State Anxiety Inventory (S-AI). After baseline assessment, participants received education about pregnancy-related anxiety and danger signs, along with audio-visual videos demonstrating five-finger hypnosis. They were instructed to practice four times per week for one month with support from family members. Results: Results showed the proportion of mothers with moderate anxiety decreased, while most participants reported mild anxiety after the intervention (73.3%). In conclusion five-finger hypnosis had an impact on the anxiety levels of pregnant women, as indicated by a p-value of 0.001. Conclusion: The study concluded that anxiety disorders during pregnancy can be prevented or reduced by offering five-finger hypnosis and effective education as non-pharmacological treatments.